(untitled) (Physical Education, Health and Social Sciences, 2025)
Equity, diversity, and inclusion (EDI) in education are essential for fostering a learning environment where all students, regardless of their backgrounds and abilities, can thrive. This study explores the role of teacher professional development in implementing EDI principles in classrooms, with a particular focus on Individualized Educational Plans (IEPs) and inclusive pedagogical strategies. Through a mixed-methods approach, data is collected from educators through surveys, classroom observations, and in-depth interviews with teachers, school leaders, and special education experts across diverse educational settings. Findings reveal that teachers who receive targeted EDI training demonstrate improved competency in adapting instructional methods to meet diverse student needs, leading to increased student engagement and participation. The research highlights that sustained professional development programs focusing on culturally responsive teaching, universal design for learning (UDL), and differentiated instruction significantly enhance teachers’ ability to create inclusive classrooms. Collaborative teaching models, peer mentoring, and ongoing reflective practices further reinforce equitable learning opportunities. The study underscores the necessity of embedding EDI-focused professional development into teacher training programs to ensure systemic, long-term impact. Policy recommendations emphasize institutional commitment to continuous teacher learning, integration of inclusive curricula, and the development of assessment frameworks to measure the effectiveness of EDI initiatives. By providing empirical evidence, this research informs future strategies for equipping educators with the necessary skills to foster equitable and inclusive learning environments, ultimately benefiting all learners.